Aging and Gender: Reconstructing Older People’s Social Roles in Care Work (Revista Rupturas, 2019)
This paper discusses the social roles of older people from a social gerontology perspective; particularly, critical gerontology. Considering the process of growing older as a gendered one, the example of care work is used to argue that an inclusive re-construction of older people’s social roles must include a critical reflection on the intersection between gender and ideas on ageing and its potentialities. Such a reflection should include the need of gathering information on the subjective assessment individuals make on what it means to be old, the potentialities of this life stage and the roles associated to it, as opposed to consider older people the passive recipients of public policy aimed at this age group.
Keywords: gender; ageing; social roles; rupturist gerontology; carework; gerontological theories